2017
DOI: 10.1371/journal.pone.0176147
|View full text |Cite
|
Sign up to set email alerts
|

Nestin expression is upregulated in the fibrotic rat heart and is localized in collagen-expressing mesenchymal cells and interstitial CD31(+)- cells

Abstract: Renal and lung fibrosis was characterized by the accumulation of collagen-immunoreactive mesenchymal cells expressing the intermediate filament protein nestin. The present study tested the hypothesis that nestin expression was increased in the hypertrophied/fibrotic left ventricle of suprarenal abdominal aorta constricted adult male Sprague-Dawley rats and induced in ventricular fibroblasts by pro-fibrotic peptide growth factors. Nestin protein levels were upregulated in the pressure-overloaded left ventricle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…However, numerous studies have reported that the intermediate filament protein is expressed in a wide variety of normal and tumorigenic cells (Oikawa et al, 2010 ; Ishiwata et al, 2011 ; Béguin et al, 2012 ; Liang et al, 2015 ; Neradil and Veselska, 2015 ). Among the various populations of cells expressing nestin, the intermediate filament protein was detected in ventricular fibroblasts and dynamically regulated during postnatal development and in the fibrotic heart secondary to an ischemic insult or pressure-overload (Béguin et al, 2012 ; Hertig et al, 2017 ). Nestin is ubiquitously expressed in neonatal rat ventricular fibroblasts and postnatal development led to a significant downregulation of the intermediate filament protein in adult rat ventricular fibroblasts (Béguin et al, 2012 ).…”
Section: Reparative/reactive Fibrosis and Nestin Expression In Ventrimentioning
confidence: 99%
See 1 more Smart Citation
“…However, numerous studies have reported that the intermediate filament protein is expressed in a wide variety of normal and tumorigenic cells (Oikawa et al, 2010 ; Ishiwata et al, 2011 ; Béguin et al, 2012 ; Liang et al, 2015 ; Neradil and Veselska, 2015 ). Among the various populations of cells expressing nestin, the intermediate filament protein was detected in ventricular fibroblasts and dynamically regulated during postnatal development and in the fibrotic heart secondary to an ischemic insult or pressure-overload (Béguin et al, 2012 ; Hertig et al, 2017 ). Nestin is ubiquitously expressed in neonatal rat ventricular fibroblasts and postnatal development led to a significant downregulation of the intermediate filament protein in adult rat ventricular fibroblasts (Béguin et al, 2012 ).…”
Section: Reparative/reactive Fibrosis and Nestin Expression In Ventrimentioning
confidence: 99%
“…An additional pathological feature of the pressure-overloaded heart is perivascular fibrosis characterized by the deposition of collagen type I within the adventitial region of the coronary vasculature leading to vascular stiffness (Dong et al, 2017 ). In the hypertrophied/fibrotic left ventricle of the rat heart secondary to pressure-overload, nestin protein levels were upregulated and attributed in part to the increased density of collagen type I-immunoreactive mesenchymal cells co-expressing the intermediate filament protein (Hertig et al, 2017 ). The increased density of nestin/collagen (+) -mesenchymal cells in the pressure-overloaded heart may be secondary to the upregulation of the intermediate filament protein in normal adult ventricular fibroblasts following exposure to the pro-fibrotic peptide growth factors angiotensin II, transforming growth factor-β 1 , and EGF (Hertig et al, 2017 ).…”
Section: Reparative/reactive Fibrosis and Nestin Expression In Ventrimentioning
confidence: 99%
“…Nestin is a member of the class VI family of intermediate filament proteins originally identified in neural progenitor/stem cells of the developing central nervous system (Dahlstrand, Zimmerman, McKay, & Lendahl, ; Lendahl, Zimmerman, & McKay, ). However, additional studies revealed that nestin was not a unique marker of neural progenitor/stem cells as the intermediate filament protein was detected in fibroblasts (e.g., heart, kidney), vascular smooth muscle and endothelial cells, pre‐existing cardiomyocytes bordering the peri‐infarct region of the ischemically damaged human/rodent heart, skeletal muscle, and tumorigenic cells (Béguin, Gosselin, Mamarbachi, & Calderone, ; Carlsson, Li, Paulin, & Thornell, ; Chen et al, ; El‐Helou et al, ; Hertig et al, ; Ishiwata et al, ; Meus, Hertig, Villeneuve, Jasmin, & Calderone, Mokry et al, ; Oikawa, Hayashi, Maesawa, Masuda, & Sobue, ; Sejersen & Lendahl, ; Tardif et al, ; Tomioka et al, ; Vaittinen et al, ). Biologically, nestin plays a direct role in the proliferation and migration of normal and tumorigenic cells (Béguin et al, ; Chen et al, ; Liang et al, ; Ishiwata, Matsuda, & Naito, ; Matsuda et al, ; Meus et al, ; Tardif et al, ; Xue & Yuan, ).…”
Section: Introductionmentioning
confidence: 99%
“…protein was detected in fibroblasts (e.g., heart, kidney), vascular smooth muscle and endothelial cells, pre-existing cardiomyocytes bordering the peri-infarct region of the ischemically damaged human/rodent heart, skeletal muscle, and tumorigenic cells (Béguin, Gosselin, Mamarbachi, & Calderone, 2012;Carlsson, Li, Paulin, & Thornell, 1999;Chen et al, 2014;El-Helou et al, 2008;Hertig et al, 2017;Ishiwata et al, 2011;Meus, Hertig, Villeneuve, Jasmin, & Calderone, 2017Mokry et al, 2004Oikawa, Hayashi, Maesawa, Masuda, & Sobue, 2010;Sejersen & Lendahl, 1993;Tardif et al, 2015;Tomioka et al, 2010;Vaittinen et al, 2001).…”
mentioning
confidence: 99%
“…More importantly, Nestin is also expressed in some adult stem/progenitor cell populations, indicating that Nestin might be a common marker of multipotent stem cells [12]. Under speci c damage conditions, upregulation of Nestin expression was found in tubular cells, podocytes, interstitial cells and brotic rat hearts [13][14][15]. More importantly,…”
Section: Introductionmentioning
confidence: 99%